Adverse Events Related to SARS-Cov-2 Vaccination: A Systematic Review and Meta-Analysis - Segun Bello; David Taiwo Ajayi; Akinmade Adepoju; Temitope Omotosho; Rotimi Felix Afolabi; Babatunde Gbadebo; Mobolaji Modinat Salawu; Eniola Adetola Bamgboye; Olabisi Oduwole; Adeniyi Fagbamigbe; Ayo Stephen Adebowale (Journal of Epidemiology and Public Health, 2023)
Background: Vaccination has been adopted as a key public health strategy for combating the COVID-19 pandemic. The accelerated SARS-CoV-2 vaccines’ development had limited time for extensive investigation of the adverse events. The study aimed to assess the average adverse events rates in published COVID-19 vaccination studies. Subjects and Method: The study used systematic review and meta-analysis involving studies that reported adverse events following administration of any of the approved COVID-19 vaccines in humans. A highly specific search strategy was developed and implemented in PubMed. The core search string was “(COVID-19 OR COVID OR "coronavirus disease") AND vaccin* AND (side-effects OR "adverse events")”. Titles and abstracts were screened, and full texts of potentially relevant articles were retrieved. Data extracted included general study background, adverse events, and frequency of occurrence. Meta-analyses were conducted for adverse events reported by at least 5 studies. Meta-analysis of proportions was carried out using logit transformation with the generalized linear mixed model estimation method. Results: A total of 108 adverse events were reported in 15 studies observing 735,515 participants from 10 countries. The highest pooled prevalence rates were pain at injection site (67.2%; 95% CI= 46.49 to 82.86; I2= 99.9%, 11 studies, 670,557 participants), weakness/fatigue (41.88%; 95% CI= 26.82 to 58.61, I2= 99.9%, 13 studies, 671,045 participants), muscle/joint pain (28.95%; 95% CI= 16.95 to 44.86, I2= 99.9%, 13 studies, 672,791 participants), and headache (27.78%; 95% CI= 17.59 to 40.95, I2= 99.9%, 14 studies, 672,883 participants). Four cases of death were reported by two papers enrolling 711 patients with cancer or multiple sclerosis, three due to comorbid disease progression, and one case due to COVID-19. Forty-three cases of anaphylaxis were reported in three studies enrolling 68,218 participants. Conclusion: The most prevalent adverse events among recipient of SARS-CoV-2 vaccines were local and general systemic reactions. Keywords: COVID-19, SARS-CoV-2 vaccine, adverse events, meta-analysis, systematic review Correspondence: Segun Bello. Department of Epidemiology and Medical Statistics, Faculty of Public Health, College of Medicine, University of Ibadan, Nigeria. Email: drsegunbello@yahoo.com.